An appraisal of the Malaysian legal framework in conserving the marine endangered species - Rahman M.A.A.; Rusli M.U.; Aziz N.; Rusli M.H.M.; Talaat W.I.A.W. (Universiti Malaysia Terengganu, 2024)
Indexed by SCOPUS